Ambient Protection of Few‐Layer Black Phosphorus via Sequestration of Reactive Oxygen Species. Issue 27 (12th May 2017) - Walia, Sumeet; Balendhran, Sivacarendran; Ahmed, Taimur; Singh, Mandeep; El‐Badawi, Christopher; Brennan, Mathew D.; Weerathunge, Pabudi; Karim, Md. Nurul; Rahman, Fahmida; Rassell, Andrea; Duckworth, Jonathan; Ramanathan, Rajesh; et al.
Abstract : Few‐layer black phosphorous (BP) has emerged as a promising candidate for next‐generation nanophotonic and nanoelectronic devices. However, rapid ambient degradation of mechanically exfoliated BP poses challenges in its practical deployment in scalable devices. To date, the strategies employed to protect BP have relied upon preventing its exposure to atmospheric conditions. Here, an approach that allows this sensitive material to remain stable without requiring its isolation from the ambient environment is reported. The method draws inspiration from the unique ability of biological systems to avoid photo‐oxidative damage caused by reactive oxygen species. Since BP undergoes similar photo‐oxidative degradation, imidazolium‐based ionic liquids are employed as quenchers of these damaging species on the BP surface. This chemical sequestration strategy allows BP to remain stable for over 13 weeks, while retaining its key electronic characteristics. This study opens opportunities to practically implement BP and other environmentally sensitive 2D materials for electronic applications. Abstract : Few‐layer black phosphorous (BP) has recently emerged as a promising elemental analog to graphene. A chemical sequestration approach is reported that allows BP to remain stable without requiring its isolation from the ambient environment. The strategy allows BP to remain stable for over 13 weeks, while retaining its key electronic characteristics.